Analisis Risiko Gangguan Pendengaran pada Pekerja Bagian Produksi Basah di PT. Hok Tong Jambi - Salsabila Salsabila; Willia Novita Eka Rini; Rd. Halim; Budi Aswin; Puspita Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of the industrial sector in Indonesia increases the risk of exposure to physical hazards such as noise, especially in the rubber processing industry. One of them is PT. Hok Tong Jambi, which shows noise levels exceeding the Threshold Limit Value (NAB) to reach 99.1 dBA. This study aims to analyze the risk of hearing loss in wet production workers. This study uses a qualitative method with a descriptive approach, data were collected from 6 informants through observation, interviews, document review and noise measurement using a Sound Level Meter. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions, in accordance with the Miles and Huberman approach. The results showed that most workers were exposed to high noise for more than 8 hours per day, with an intensity exceeding 85 dBA, and minimal use of ear protection. Early symptoms such as tinnitus and headaches were reported by workers. The risk of hearing loss in wet production workers at PT. Hok Tong Jambi is high and real. This study emphasizes the importance of comprehensive noise control that includes technical, administrative, and educational approaches. These findings are expected to be the basis for strengthening OHS policies and developing participatory interventions based on field contexts.